KETERAMPILAN MENULIS KREATIF DAN KREATIVITAS PESERTA DIDIK SD DALAM PEMBELAJARAN TEMATIK MUATAN BAHASA INDONESIA MELALUI PENERAPAN MODEL PROJECT BASED LEARNING - Jaenudin, Jaenudin; Cahyani, Isah; Budiastra, Ketut (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This research aims to investigate the creative writing skills and creativity of elementary school students in thematic learning of Indonesian language content through the implementation of the project-based learning model. The research employs a weak experimental method with a single-group, pre-test, and post-test design. The population consists of 29 fifth-grade students from Cibadak State Elementary School, Rancabali Subdistrict, Bandung District. The instruments used include a pre-test to assess cognitive levels, an observation sheet to measure students' creativity and the application of project-based learning, and a questionnaire to collect feedback from the students. The results of the research show that the implementation of the project-based learning model can improve creative writing skills and develop students' creativity. The N-Gain result is 0.69, which falls within the moderate category. The conclusion of the research reveals significant average scores with a benchmark of 70. Students' creativity during the learning process is at 61%, with most students falling within the